2021
DOI: 10.1109/jtehm.2021.3098127
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Wearable Device for Continuous Temperature Monitoring & Fever Detection

Abstract: This work involved human subjects in its research. Approval of all ethical and experimental procedures and protocols was granted by the Mayo Clinic Institutional Review Board Department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Although data from the temperature sensor is not used for extracting STIs, it is still a useful biometric for detecting fever. [ 25 ] The temperature sensor accuracy was compared to a standard thermistor (TMD‐56, Amprobe) over a wide range of temperatures and was found to have very little error (0.14 ± 0.07~°C, Figure , Supporting Information). To achieve high accuracy in detecting STIs the sampling interval must be free of variability.…”
Section: Resultsmentioning
confidence: 99%
“…Although data from the temperature sensor is not used for extracting STIs, it is still a useful biometric for detecting fever. [ 25 ] The temperature sensor accuracy was compared to a standard thermistor (TMD‐56, Amprobe) over a wide range of temperatures and was found to have very little error (0.14 ± 0.07~°C, Figure , Supporting Information). To achieve high accuracy in detecting STIs the sampling interval must be free of variability.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, although such technology might have some limitations in providing an assessment of core body temperature during exercise and its precision should be further evaluated [37][38][39], it might be useful for detecting hyperthermic events in the clinical setting, particularly when compared to other non-invasive methods which might not provide continuous temperature readings [40][41][42] or when patients have to be remotely monitored [1,[43][44][45][46]. Our results showed that a novel non-invasive wireless heat flux-based thermometer was able to detect body temperature changes measured by the tympanic thermometer as the presence or absence of hyperthermia (94.1%) and the presence or absence of fever (97.4%) in the post-stroke clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…One case series described three patients who were monitored at home with a device that detected a fever even when an oral temperature was not detected by traditional methods, and two of those cases were associated with bloodstream infections. These technologies could trigger the earlier initiation of antibiotics and lead to a lower risk of severe infectious complications without the need for prophylaxis and its attendant risks [43 ▪ ,44].…”
Section: Risk-assessment Strategies and Future Methods To Guide Antib...mentioning
confidence: 99%